Managing factors influence defects on industrialized building system (IBS) components towards sustainability construction / Nur Syamira Sapri and Mohd Nurfaisal Baharuddin - Sapri, Nur Syamira; Baharuddin, Mohd Nurfaisal (2018)
Industrialized Building System (IBS) is a one of the popular construction systems in Malaysia. It is a method of construction which involves prefabricated components and on-site installation of manufactured construction products using a specialized technique to create components or building systems. The aim of this study was to reduce defects on IBS components as well as to achieve a successful project. To achieve for the above aim, the following objectives have been identified which were to identify the factors that may lead defects on IBS components and to propose recommendations in order to reduce defects on the building components. For the first objective, an extensive literature review was conducted in a way to find most common factors which influence defects on IBS components among the scholars, while for the second objective all the data gathered from first phase interview were analyzed. The purpose of the objectives was to understand the factors influencing or the barrier which affect the occurrences of defects on building components. To make this research a success, there were four stages which were, the literature review, two methods of data collection where by data collection method through interview sessions as to validate a parameter and followed by second phase of data collection which was questionnaire survey, result, analysis and findings and lastly the conclusion and recommendation. For this paper, only the first phase of data collection method was discussed. The findings obtained showed that there are about five factors that influence defects on IBS components. The findings of this study help the manufacturers or contractors in industry to avoid defects on IBS components in achieving sustainability agenda in construction as outlined by Construction Industry Transformation Programme (CITP) 2016 as well asby Construction Industry Development Board (CIDB).